Adhesive and manufacturing method thereof, separator, electrode plate, electrode assembly, battery cell, battery, and power consuming device

JP2025505481AActive Publication Date: 2025-02-28CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024520581
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2023-06-02
Publication Date
2025-02-28
Estimated Expiration
2043-06-02

AI Technical Summary

Benefits of technology

を有し、ここでこれ以上説明しない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505481000001_ABST
    Figure 2025505481000001_ABST
Patent Text Reader

Abstract

This application discloses an adhesive and its manufacturing method, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consumption device, and relates to the field of battery technology. The adhesive includes a coating layer and a core disposed within the coating layer, where the coating layer includes a polyacrylate-based copolymer, and the core includes a ceramic. When the adhesive is applied to a separator and used in a battery, it has strong adhesion, improves the cold press adhesion of the battery core and the hardness of the battery core, reduces the electrochemical impedance, and improves the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of battery technology, and in particular to adhesives and their manufacturing methods, separators, plates, electrode assemblies, battery cells, batteries, and power consuming devices.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Chinese patent application No. 202310010277.1, proposed on January 4, 2023, for "Adhesive and Manufacturing Method Therefor, Separator, Electrode Plate, Electrode Assembly, Battery Cell, Battery, and Power Consumption Device," the entire contents of which are incorporated herein by reference. [Background technology]

[0003] In recent years, as the application range of batteries becomes wider and wider, batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. However, the battery adhesives used in conventional technologies have problems such as poor adhesion performance and low hardness, which further causes the battery components to be unable to be effectively bonded, thereby deteriorating the cycle performance of the battery and causing safety issues. Summary of the Invention

[0004] The present application has been made in view of the above problems, and aims to provide a material that can provide good adhesive performance under conditions suitable for battery processing, thereby contributing to increasing the hardness and cycle performance of the battery core.

[0005] To achieve the above objective, the present application provides an adhesive and a manufacturing method thereof, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consuming device.

[0006] According to a first aspect, the present application provides an adhesive, the adhesive comprising a coating layer and a core disposed within the coating layer, wherein the coating layer comprises a polyacrylate-based copolymer and the core comprises a ceramic.

[0007] Therefore, the technical solution of the embodiment of the present application includes a coating layer and a core disposed within the coating layer, where the coating layer includes a polyacrylate copolymer and the core includes a ceramic material. When the adhesive is applied to a separator and used in a battery, it has a strong adhesive property, which can improve the cold press adhesive force of the battery core and the hardness of the battery core, reduce the electrochemical impedance, and improve the cycle performance of the battery.

[0008] In any embodiment, the polyacrylate copolymer monomers include acrylate monomers, acrylonitrile monomers, and acrylamide monomers.

[0009] Thus, the acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a cyano group with strong polarity and contributes to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0010] In any of the embodiments, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15). By controlling the molar ratio of the above three monomers within the above ranges, the molecular weight and the glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0011] In any one of the embodiments, the acrylate monomer is methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide. Experiments have shown that the above-mentioned three monomers have good lithium replenishment and adhesion effects, and further improve the cycle performance and power supply performance of lithium ion batteries.

[0012] In any one of the embodiments, the mass ratio of the polyacrylate copolymer to the ceramic is (20-50):(50-80). At the above blending ratio, the adhesive can have an excellent adhesive effect.

[0013] In any of the embodiments, the ceramics include at least one of titanium dioxide, silicon dioxide, boehmite, magnesium oxide, and aluminum oxide, and the ceramics can be used to improve the cold press adhesion of the battery core and the hardness of the battery core, reduce the electrochemical impedance, and improve the cycle performance of the battery.

[0014] In any one of the embodiments, the ceramic has a volume average particle diameter Dv50 of 0.01 μm to 2 μm. With this particle diameter, the adhesive has a strong adhesive force, and the cycle performance of the battery is improved.

[0015] In any one of the embodiments, the adhesive has a volume average particle diameter Dv50 of 5 to 100 μm, and optionally 7 to 8 μm. In the above particle diameter range, the adhesive has a good adhesive effect.

[0016] According to a second aspect, the present application provides a method for producing an adhesive, the method including the steps of: adding a monomer of a polyacrylate copolymer to a solution containing an emulsifier to obtain a preliminary emulsion; adding an initiator to the preliminary emulsion to react with the resulting mixture, and then adjusting the pH value to 7 to 8 to obtain a reaction liquid; and uniformly mixing the reaction liquid with ceramics and then drying to obtain the adhesive.

[0017] Emulsion polymerization has a fast polymerization speed, and is favorable for heat conduction and temperature control. After the reaction reaches a high conversion rate, the viscosity of the emulsion polymerization system is still very low, and the dispersion system is stable, making it easy to control and realize continuous operation. In addition, the polymer and ceramic particles can be mixed and coated to produce a core-shell structure adhesive, which can improve the stability of the adhesive, and the ceramic particles can be bonded with the polymer during cold pressing, which can increase the adhesive strength of the cold pressing and improve the dynamic performance of the lithium-ion battery.

[0018] In any embodiment, the reaction temperature is 20 to 90°C, and optionally 75 to 85°C, and the reaction time is 20 to 40 minutes. As is clear from experiments, the reaction is more sufficient and side reactions are less at the above reaction temperature and time.

[0019] The drying includes spray drying. Spray drying is one of the methods that systematization technology uses to dry materials. After the thinner is atomized in the drying chamber, the water evaporates quickly in contact with hot air to obtain a dried product. This method can directly dry the solution or emulsion into a powder or granular product, and can omit the steps of evaporation, grinding, etc. The drying process is very fast, can directly dry into powder, and is easy to change the drying conditions, adjust the quality specifications of the product, and evaporate instantly, so the requirements for the selection of equipment materials are not strict. The drying chamber has a certain negative pressure, which ensures the sanitary conditions in production, avoids dust from flying on site, and improves product purity.

[0020] In any embodiment, the polyacrylate copolymer monomers include acrylate monomers, acrylonitrile monomers, and acrylamide monomers.

[0021] Thus, the acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a cyano group with strong polarity and contributes to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0022] In any embodiment, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12). By controlling the molar ratio of the three monomers within the above ranges, the molecular weight and the glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0023] In any embodiment, the acrylate monomer comprises at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate; the acrylonitrile monomer comprises at least one of acrylonitrile and methacrylonitrile; the acrylamide monomer comprises at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide; and it is found by experiments that the above-mentioned materials are used as the three monomers, which have good adhesion effect and further improve the cycle performance and power supply performance of lithium ion batteries.

[0024] In any one of the embodiments, the mass ratio of the polyacrylate copolymer to the ceramic is (20-50):(50-80). At the above blending ratio, the adhesive can have an excellent adhesive effect.

[0025] In any of the embodiments, the ceramics include at least one of titanium dioxide, silicon dioxide, boehmite, magnesium oxide, and aluminum oxide, and the ceramics can be used to improve the cold press adhesion of the battery core and the hardness of the battery core, reduce the electrochemical impedance, and improve the cycle performance of the battery.

[0026] In any one of the embodiments, the ceramic has a volume average particle diameter Dv50 of 0.01 μm to 2 μm. With this particle diameter, the adhesive has a strong adhesive force, and the cycle performance of the battery is improved.

[0027] In any one of the embodiments, the adhesive has a volume average particle diameter Dv50 of 5 to 100 μm, and optionally 7 to 8 μm. In the above particle diameter range, the adhesive has a good adhesive effect.

[0028] According to a third aspect, an embodiment of the present application provides a separator, the separator comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0029] According to a fourth aspect, an embodiment of the present application provides a plate, the plate comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0030] According to a fifth aspect, an embodiment of the present application provides an electrode assembly, the electrode assembly including at least one of an adhesive according to an embodiment of the first aspect of the present application, an adhesive manufactured by the manufacturing method for an adhesive according to an embodiment of the second aspect, a separator according to an embodiment of the third aspect, and an electrode plate according to an embodiment of the fourth aspect.

[0031] According to a sixth aspect, an embodiment of the present application provides a battery cell, the battery cell including an electrode assembly according to the embodiment of the fifth aspect of the present application.

[0032] According to a seventh aspect, an embodiment of the present application provides a battery, the battery including a battery cell according to an embodiment of the sixth aspect of the present application.

[0033] According to an eighth aspect, an embodiment of the present application provides a power consuming device, the power consuming device comprising a battery cell according to an embodiment of the sixth aspect of the present application or a battery according to an embodiment of the seventh aspect. [Brief description of the drawings]

[0034] In order to more clearly explain the technical solutions in the embodiments of the present invention or the prior art, the following briefly introduces drawings that need to be used in the embodiments or prior art description. It is obvious that the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can also obtain other related drawings based on these drawings without exerting creative efforts. [Figure 1] FIG. 1 is a schematic diagram of a battery cell according to one embodiment of the present application. [Diagram 2] FIG. 2 is an exploded view of the battery cell according to the embodiment of the present application shown in FIG. [Diagram 3] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 4] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6] 1 is a schematic diagram of a power consumption device powered by a secondary battery according to an embodiment of the present application; [Figure 7] FIG 2 is a SEM image of the adhesive of Example 1 of the present application. The realization of the objects, functional features and advantages of the present invention will be further explained with reference to the drawings in conjunction with the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the adhesive, separator, electrode plate, electrode assembly, battery cell, battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0036] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0037] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0038] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0039] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0040] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.

[0041] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0042] The inside of a secondary battery is composed of a positive electrode plate, a negative electrode plate, a separator and an electrolyte. Due to the requirements of the manufacturing process and the optimization of the battery core performance, it is necessary to provide a certain adhesive force between the positive electrode plate, the negative electrode plate and the separator, which can be achieved by applying an adhesive coating material to the separator surface to produce an adhesive separator. In the current technology, the material applied to the separator surface can be divided into fluorine-containing polymers and non-fluorine-containing polymers.

[0043] In recent years, as the application range of batteries becomes wider and wider, batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. However, the battery adhesives used in conventional technologies have problems such as poor adhesion performance and low hardness, which further causes the battery components to be unable to be effectively bonded, thereby deteriorating the cycle performance of the battery and causing safety issues.

[0044] In view of this, researchers have made a series of improvements to the method of coating ceramic particles with a polymer and its application, providing a method, which comprises dispersing ceramic particles in an organic solvent and adding a coupling agent to disperse the ceramic particles to form a first dispersion, dissolving a first polymer and a second polymer in an organic solvent to form a second dispersion, reacting the first dispersion with the second dispersion to form a third dispersion, mixing the first dispersant, an organic solvent and water to form a base liquid, simultaneously dropping the aqueous solution of the third dispersion and the aqueous solution of the second dispersant into the base liquid, and the water-oil ratio of the third dispersion and the aqueous solution of the second dispersant is the same as that of the base liquid. The first polymer is at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer, and the second polymer is at least one of polyacrylonitrile, polyacrylic acid and polyacrylate copolymer.

[0045] Polyvinylidene fluoride is the most commonly used adhesive and is widely used on separators, but at present, the price of polyvinylidene fluoride has risen significantly, and the market is selling well and the supply cannot keep up. Polyvinylidene fluoride polymer can be coated on the surface of lithium battery separator to solve part of the separator's high temperature shrinkage problem, and cold pressing is performed after winding the battery core, but general polyvinylidene fluoride is a homopolymer with a crystallinity of about 50%, which causes insufficient adhesion with the positive and negative electrodes, and the battery core opening problem always occurs.

[0046] Based on this, the inventors have discovered after a large amount of experiments that the organic polymer obtained by polymerizing polymer monomers containing specific functional groups in a certain weight ratio has good adhesive performance and is suitable for fully exerting its adhesive performance under battery working conditions, thereby contributing to improving the cycle performance of secondary batteries. It can be used in combination with ceramic particles to increase the hardness of the battery core. Moreover, when the adhesive is used in a separator, it can reduce the resistance of the separator and contribute to increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0047] Based on this, the present application provides an adhesive and a manufacturing method thereof, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consuming device.

[0048] The present application provides an adhesive, the adhesive including a coating layer and a core disposed within the coating layer, where the coating layer includes a polyacrylate-based copolymer and the core includes a ceramic.

[0049] Therefore, the technical solution of the embodiment of the present application includes a coating layer and a core disposed within the coating layer, where the coating layer includes a polyacrylate copolymer and the core includes a ceramic material. When the adhesive is applied to a separator and used in a battery, it has a strong adhesive property, which can improve the cold press adhesive force of the battery core and the hardness of the battery core, reduce the electrochemical impedance, and improve the cycle performance of the battery.

[0050] Polyacrylate copolymer is a general term for polymers produced through copolymerization reaction using acrylate as raw material. Acrylate has active double bonds and is easy to self-polymerize and copolymerize. The copolymerization monomer may be one or more, and may be another acrylic acid compound or other unsaturated compound with double bonds, such as styrene, acrylonitrile, vinyl acetate, vinyl chloride, etc.

[0051] Ceramics refers to inorganic non-metallic materials manufactured by molding and high-temperature sintering using natural or synthetic compounds. It has the advantages of high melting point, high hardness, high wear resistance, oxidation resistance, etc. It can be made by sintering natural raw materials such as feldspar, clay and quartz, and is a typical silicate material. The main composition elements are silicon, aluminum and oxygen, and these three elements account for 90% of the total amount of elements in the earth's crust. Ordinary ceramics have abundant sources, low costs and mature processes. According to their performance characteristics and applications, such ceramics can be divided into daily ceramics, architectural ceramics, electrical insulating ceramics, chemical industry ceramics, etc.

[0052] In any embodiment, the polyacrylate copolymer monomers include acrylate monomers, acrylonitrile monomers, and acrylamide monomers.

[0053] The acrylate monomer is a monomer containing an acrylate group, and its simplified structural formula is as follows: TIFF2025505481000002.tif30129 Here, R1 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, R2 includes a substituted or unsubstituted alkyl group of 1 to 15 carbon atoms, a cycloalkyl group of 3 to 6 carbon atoms, or an isobornyl group, and in the case of substitution, the substituent includes a hydroxyl group or an alkyl group of 1 to 6 carbon atoms.

[0054] The acrylonitrile monomer is a monomer containing an acrylonitrile group, and its simplified structural formula is as follows: TIFF2025505481000003.tif30129 Here, R3 comprises a hydrogen atom or an alkyl group of 1 to 6 carbon atoms.

[0055] An acrylamide monomer is a monomer containing an acrylamide group, and its simplified structural formula is as follows: TIFF2025505481000004.tif30129 Here, R4 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 includes a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms.

[0056] Thus, the acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a cyano group with strong polarity and contributes to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0057] As can be understood, the present application is not limited to the numbering method of each monomer in the polyacrylate copolymer, and the acrylate monomer, the acrylonitrile monomer and the acrylamide monomer may be arranged in order, or the three monomers may be arranged randomly, and all of the above methods are within the scope of protection of the present application.

[0058] In any embodiment, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12). For example, it may be any one of the following points or any two range values: 1:0.01:0.01, 1:0.01:0.15, 1:0.8:0.01, 1:0.8:0.15, 1:0.4:0.01, 1:0.4:0.15, 1:0.01:0.08, 1:0.8:0.08, but is not limited thereto. By controlling the molar ratio of the above three monomers within the above range, the molecular weight and glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0059] In any embodiment, the acrylate monomer comprises at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate; the acrylonitrile monomer comprises at least one of acrylonitrile and methacrylonitrile; the acrylamide monomer comprises at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide; and it is found by experiments that the above-mentioned materials are used as the three monomers, which have good adhesion effect and further improve the cycle performance and power supply performance of lithium ion batteries.

[0060] In any embodiment, the mass ratio of the polyacrylate copolymer to the ceramic is (20-50):(50-80). For example, the mass ratio may be any one of 20:50, 20:80, 20:65, 50:50, 50:80, and 50:65, or a range between any two of these, but is not limited thereto. With the above blending ratio, the adhesive can have excellent adhesive effect.

[0061] In any of the embodiments, the ceramics include at least one of titanium dioxide, silicon dioxide, boehmite, magnesium oxide, and aluminum oxide, and the ceramics can be used to improve the cold press adhesion of the battery core and the hardness of the battery core, reduce the electrochemical impedance, and improve the cycle performance of the battery.

[0062] In any of the embodiments, the ceramic has a volume average particle diameter Dv50 of 0.01 μm to 2 μm. For example, the volume average particle diameter Dv50 may be any one of 0.01 μm, 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 1.8 μm, and 2 μm, or a range value between any two of these, but is not limited thereto. With the above particle diameter, the adhesive has a strong adhesive force and improves the cycle performance of the battery.

[0063] In any of the embodiments, the adhesive has a volume average particle diameter Dv50 of 5 to 100 μm, and optionally 7 to 8 μm. For example, the volume average particle diameter Dv50 may be any one of 5 μm, 7 μm, 8 μm, 10 μm, 30 μm, 50 μm, 80 μm, and 100 μm, or a range value between any two of these, but is not limited thereto. In the above particle diameter range, the adhesive effect is good.

[0064] In the embodiment of the present application, the particle size corresponding to when the cumulative particle size distribution percentage of the adhesive particles reaches 50% is Dv50, and the test method is as follows:

[0065] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. Use a laser granulometer (Malvern 3000, MasterSizer 3000) to test, and use a helium-neon red light source as the main light source. Take one clean small beaker, add 1g of the sample to be tested, add one drop of surfactant, add 20ml of deionized water (ensure the sample concentration is 8-12% light blocking), and sonicate at 53KHz / 120W for 5 minutes to ensure the sample is completely dispersed. Turn on the laser granulometer and test the background automatically after cleaning the light path system. Stir the already sonicated solution to be tested, disperse it evenly, and put it into the sample pool as required, and start to measure the particle size. The measurement result can be read from the instrument.

[0066] According to a second aspect, the present application provides a method for producing an adhesive, the method including the steps of: adding a monomer of a polyacrylate copolymer to a solution containing an emulsifier to obtain a preliminary emulsion; adding an initiator to the preliminary emulsion to react with the resulting mixture, and then adjusting the pH value to 7 to 8 to obtain a reaction liquid; and uniformly mixing the reaction liquid with ceramics and then drying to obtain the adhesive.

[0067] Emulsifiers are substances such as organic compounds that form incompatible liquids into a stable emulsion. They are all surface-active substances that can reduce the interfacial tension between liquids, making it easier to emulsify incompatible liquids. During emulsification, the dispersed phase is uniformly distributed in the continuous phase in the form of very small liquid beads (with diameters between 0.1 microns and tens of microns), and the emulsifier forms a film or double electrical layer on the surface of these liquid beads to prevent them from coagulating with each other and maintain the stability of the emulsion. In the embodiment of this application, the emulsifier employed is sodium dodecyl sulfonate.

[0068] The pre-emulsion is a solution formed after emulsifying the monomers of the polyacrylate copolymer to form a stable emulsion of the monomers.

[0069] The initiator, also called a radical initiator, refers to a substance such as a compound that is easily decomposed into radicals (i.e., primary radicals) when exposed to heat, and may be used to initiate the radical polymerization and copolymerization reactions of ene and diene monomers, and may be used in the crosslinking curing and polymer crosslinking reactions of unsaturated polyesters. In the embodiment of the present application, the initiator employed is potassium persulfate.

[0070] The value of the hydrogen ion concentration index is generally called the "pH value." The value that indicates the degree of acidity or alkalinity of a solution is the negative value of the common logarithm of the hydrogen ion concentration contained. The pH value can be measured using pH test paper or a pH meter.

[0071] Emulsion polymerization has a fast polymerization speed, and is favorable for heat conduction and temperature control. After the reaction reaches a high conversion rate, the viscosity of the emulsion polymerization system is still very low, and the dispersion system is stable, making it easy to control and realize continuous operation. In addition, the polymer and ceramic particles can be mixed and coated to produce a core-shell structure adhesive, which can improve the stability of the adhesive, and the ceramic particles can be bonded with the polymer during cold pressing, which can increase the adhesive strength of the cold pressing and improve the dynamic performance of the lithium-ion battery.

[0072] As can be understood by those skilled in the art, in the above method of the specific embodiment, the order of making each step is not meant to be performed in strict order and constitutes any limitation on the order of execution, and the specific order of execution of each step should be determined by its function and possible underlying logic.

[0073] In any embodiment, the reaction temperature is 20 to 90°C, and optionally 75 to 85°C, and may be, for example, any one of the points of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 75°C, 80°C, 85°C, and 90°C, or a range value between any two of them, but is not limited thereto. The reaction time is 20 to 40 minutes, and may be, for example, any one of the points of 20 minutes, 22 minutes, 25 minutes, 28 minutes, 30 minutes, 33 minutes, 35 minutes, 37 minutes, and 40 minutes, or a range value between any two of them, but is not limited thereto. As is clear from experiments, the reaction is more complete and side reactions are less at the above reaction temperature and time.

[0074] As can be understood, the above reaction temperature and reaction time limitations may be satisfied either alone or simultaneously, and in the embodiments of the present application, both are satisfied simultaneously to make the reaction more complete and the side reactions less.

[0075] The drying includes spray drying. Spray drying is one of the methods that systematization technology uses to dry materials. After the thinner is atomized in the drying chamber, the water evaporates quickly in contact with hot air to obtain a dried product. This method can directly dry the solution or emulsion into a powder or granular product, and can omit the steps of evaporation, grinding, etc. The drying process is very fast, can directly dry into powder, and is easy to change the drying conditions, adjust the quality specifications of the product, and evaporate instantly, so the requirements for the selection of equipment materials are not strict. The drying chamber has a certain negative pressure, which ensures the sanitary conditions in production, avoids dust from flying on site, and improves product purity.

[0076] In any embodiment, the polyacrylate copolymer monomers include acrylate monomers, acrylonitrile monomers, and acrylamide monomers.

[0077] Thus, the acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a cyano group with strong polarity and contributes to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0078] In any embodiment, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).

[0079] The molar ratio of the monomers is the ratio of the mole numbers of the monomers, and may be, for example, any one of the following points or any two range values: 1:0.01:0.01, 1:0.01:0.15, 1:0.8:0.01, 1:0.8:0.15, 1:0.4:0.01, 1:0.4:0.15, 1:0.01:0.08, 1:0.8:0.08, but is not limited thereto. The molar ratio of the above three monomers is controlled within the above range, and the molecular weight and glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0080] In any one of the embodiments, the acrylate monomer is methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide. Experiments have shown that the above-mentioned three monomers have good lithium replenishment and adhesion effects, and further improve the cycle performance and power supply performance of lithium ion batteries.

[0081] In any embodiment, the mass ratio of the polyacrylate copolymer to the ceramic is (20-50):(50-80). For example, the mass ratio may be any one of 20:50, 20:80, 20:65, 50:50, 50:80, and 50:65, or a range between any two of these, but is not limited thereto. With the above blending ratio, the adhesive can have excellent adhesive effect.

[0082] In any of the embodiments, the ceramics include at least one of titanium dioxide, silicon dioxide, boehmite, magnesium oxide, and aluminum oxide, and the ceramics can be used to improve the cold press adhesion of the battery core and the hardness of the battery core, reduce the electrochemical impedance, and improve the cycle performance of the battery.

[0083] In any of the embodiments, the ceramic has a volume average particle diameter Dv50 of 0.01 μm to 2 μm. For example, the volume average particle diameter Dv50 may be any one of 0.01 μm, 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 1.8 μm, and 2 μm, or a range value between any two of these, but is not limited thereto. With the above particle diameter, the adhesive has a strong adhesive force and improves the cycle performance of the battery.

[0084] In any of the embodiments, the adhesive has a volume average particle diameter Dv50 of 5 to 100 μm, and optionally 7 to 8 μm. For example, the volume average particle diameter Dv50 may be any one of 5 μm, 7 μm, 8 μm, 10 μm, 30 μm, 50 μm, 80 μm, and 100 μm, or a range value between any two of these, but is not limited thereto. In the above particle diameter range, the adhesive effect is good.

[0085] In the embodiment of the present application, the particle size corresponding to when the cumulative particle size distribution percentage of the adhesive particles reaches 50% is Dv50, and the test method is as follows:

[0086] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. Use a laser granulometer (Malvern 3000, MasterSizer 3000) to test, and use a helium-neon red light source as the main light source. Take one clean small beaker, add 1g of the sample to be tested, add one drop of surfactant, add 20ml of deionized water (ensure the sample concentration is 8-12% light blocking), and sonicate at 53KHz / 120W for 5 minutes to ensure the sample is completely dispersed. Turn on the laser granulometer and test the background automatically after cleaning the light path system. Stir the already sonicated solution to be tested, disperse it evenly, and put it into the sample pool as required, and start to measure the particle size. The measurement result can be read from the instrument.

[0087] According to a third aspect, an embodiment of the present application provides a separator, the separator comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0088] When the adhesive of the first aspect of the present application is used in a separator, it can reduce the resistance of the separator and contribute to increasing the ionic conductivity of the separator, thereby improving battery performance and effectively replenishing lithium.

[0089] The present application is not particularly limited to the type of separator substrate, and any known porous structure separator substrate having good chemical stability and mechanical stability can be selected.

[0090] In some embodiments, the separator substrate may be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film, without any particular limitation. When the separator is a multilayer composite film, the materials of each layer may be the same or different, without any particular limitation.

[0091] The separator of the present application can be manufactured by adopting a conventional method for separators in the art, for example, the adhesive described in the first embodiment of the present application can be dissolved in an organic solvent to obtain a slurry, and the slurry can be applied onto a separator material, and then the organic solvent can be removed by drying, that is, the separator of the present application can be obtained.

[0092] In some embodiments, the adhesive has a coating density on the separator substrate of 0.3-1.0 g / m 2 and 0.3-0.8 g / m 2 It is.

[0093] According to a fourth aspect, an embodiment of the present application provides a plate, the plate comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0094] It includes the adhesive according to the embodiment of the first aspect of the present application or the adhesive produced by the method for producing the adhesive according to the embodiment of the second aspect of the present application. The electrode plate can be produced by a method commonly used in the art.

[0095] It should be explained that the electrode plate of the present application may be a positive electrode plate or a negative electrode plate.

[0096] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the adhesive of the first aspect of the present application.

[0097] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and a positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0098] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0099] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. For example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.3 Mn 0.2 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co 0.2 Mn 0.2O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0100] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive described in the examples of the first aspect of the present application, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.

[0101] In some embodiments, the loading of the adhesive described in the examples of the first aspect of the present application in the positive electrode plate is 1-3%, calculated based on the total weight of the positive electrode membrane layer.

[0102] Similarly, the electrode plate of the present application may be a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including the adhesive according to the first aspect of the present application.

[0103] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0104] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0105] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, a silicone-based material, a tin-based material, and lithium titanate. The silicone-based material may be selected from at least one of a silicone element, a silicone oxide, a silicone carbon composite, a silicone nitrogen composite, and a silicone alloy. The tin-based material may be selected from at least one of a tin element, a tin oxide, and a tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0106] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0107] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0108] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as the negative electrode active material, the conductive agent, the adhesive described in the examples of the first aspect of the present application, and any other components are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0109] In some embodiments, the amount of the adhesive described in the examples of the first aspect of the present application in the negative plate is 1-3%, calculated based on the total weight of the negative membrane layer.

[0110] According to a fifth aspect, an embodiment of the present application provides an electrode assembly, which comprises at least one of the adhesive of the first aspect of the present application, the adhesive manufactured by the adhesive manufacturing method described in the second aspect of the present application, the separator of the third aspect of the present application, and the electrode plate of the fourth aspect of the present application. The electrode assembly proposed in the present application has all the beneficial effects of the adhesives described above and will not be further described here.

[0111] According to a sixth aspect, an embodiment of the present application provides a battery cell, the battery cell including an electrode assembly according to the embodiment of the fifth aspect of the present application.

[0112] Generally, a battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to store and release ions. The electrolyte functions to conduct ions between the positive electrode plate and the negative electrode plate. The separator is installed between the positive electrode plate and the negative electrode plate, and mainly functions to prevent short circuit between the positive and negative electrodes and allows ions to pass through.

[0113] The battery cell can be manufactured by a method commonly used in the art. For example, a positive electrode plate, a negative electrode plate and a separator can be manufactured into an electrode assembly by a winding process or a lamination process, and an electrolyte is injected into the electrode assembly and sealed to manufacture the battery cell.

[0114] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.

[0115] In some embodiments, the electrolyte is an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.

[0116] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0117] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0118] In some embodiments, the electrolyte solution may further include optional additives, for example, additives for forming a negative electrode film, additives for forming a positive electrode film, and additives for improving some performance of the battery, such as additives for improving the overcharge performance of the battery, additives for improving the high temperature or low temperature performance of the battery, etc.

[0119] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.

[0120] In some embodiments, the battery cell may include an exterior body that may be used to package the electrode assembly and electrolyte.

[0121] In some embodiments, the battery cell housing may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The battery cell housing may be a pouch, such as a bag-like pouch. The pouch may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0122] The present application is not particularly limited to the shape of the battery cell, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a battery cell 5 with a rectangular structure as an example.

[0123] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the battery cell 5 may be one or more, and can be selected by those skilled in the art according to specific actual needs.

[0124] According to a seventh aspect, an embodiment of the present application provides a battery, the battery including a battery cell according to an embodiment of the sixth aspect of the present application.

[0125] The specific form of the battery may be a battery module or a battery pack, and the number of battery cells included in the battery module may be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0126] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, a plurality of battery cells 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, the battery cells 5 may be arranged in any other manner. Furthermore, the plurality of battery cells 5 may be fixed by fasteners.

[0127] In either embodiment, the battery module 4 may further include a housing having an accommodating space, and the multiple battery cells 5 are accommodated in the accommodating space.

[0128] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by one skilled in the art according to the application and capacity of the battery pack.

[0129] 4 and 5 show an example of a battery pack 1. Referring to FIG. 4 and FIG. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0130] According to an eighth aspect, an embodiment of the present application provides a power consuming device, the power consuming device including a battery cell according to the embodiment of the sixth aspect of the present application or a battery according to the embodiment of the seventh aspect of the present application. The battery cell and the battery may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0131] The power consumption device can be a secondary battery, a battery module, or a battery pack depending on its usage demand.

[0132] 6 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power output and high energy density of the secondary battery of the power consumption device.

[0133] Another example of the device may be a mobile phone, a tablet computer, a notebook computer, etc. These devices are generally required to be thin, and may employ a secondary battery as a power source.

[0134] The technical solution of the present invention will be described in more detail below in conjunction with specific examples and drawings. It should be understood that the following examples are only for interpreting the present invention, and are not intended to limit the present invention.

[0135] The relevant parameters of the adhesives of Examples 1 to 18 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0136] TIFF2025505481000005.tif250140

[0137] Example 1 1.Adhesive manufacturing (1) In a 500 ml three-neck flask, add 150 g of deionized water and 3.6 g of sodium dodecylsulfonate, and emulsify by thoroughly stirring for 15 minutes. Then, add 75.24 g of methyl acrylate, 18.55 g of acrylonitrile, and 6.21 g of acrylamide in that order, with a molar ratio of the three being 1:0.4:0.1. Stir thoroughly for 60 minutes to obtain a preliminary emulsion of monomers, which is taken out and kept as a reserve. (2) Add 100ml deionized water and 0.15g sodium dodecylbenzenesulfonate into a 500ml three-neck flask, heat to 80℃, emulsify for 15 minutes at a rotation speed of 2000r / min, make the system fully emulsified, and then slowly add the preliminary emulsion prepared in the previous step and the initiator solution (0.2g of the initiator potassium persulfate dissolved in 30g of deionized water to form a solution). After the addition is completed, increase the temperature to 90℃ and keep warm for 0.5h to react, cool to 40℃, adjust the pH to 7 with ammonia water, stop stirring, filter, and discharge the material to obtain a polymer emulsion; (3) 100 g of the above emulsion containing the polymer active ingredient and 100 g of boehmite ceramic particles with a Dv50 of 0.01 μm were dispersed at high speed for 60 minutes, stirred uniformly, and then spray-dried to obtain an adhesive with a core-shell structure.

[0138] 2. Manufacturing of separators A commercially available PP-PE copolymer microporous film (manufactured by Zhuo Gao Electronics Technology Co., Ltd., model no. 20) with a thickness of 20 μm and an average pore diameter of 80 nm was used as the substrate. The adhesive prepared above was stirred and mixed uniformly with deionized water to obtain a slurry (solid content 20%). The slurry was uniformly coated on two surfaces of the substrate and dried to remove the solvent, and the coating density of the coating composition on the substrate was 1.0 g / m 2 Thus, a separator was obtained.

[0139] 3. Manufacturing of positive electrode plates Polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), carbon black as a conductive agent, and N-methylpyrrolidone (NMP) were mixed homogeneously in a mass ratio of 1.2:58.38:0.42:40, and then prepared into a positive electrode slurry. 2 The aluminum foil positive electrode current collector was uniformly coated with the coating material in an amount of 0.1 to 1000g, and then dried, cold pressed, and slit to obtain a positive electrode plate.

[0140] 4. Manufacturing of negative electrode plates Artificial graphite, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethylcellulose (CMC-Na) as a thickener were added to deionized water in a mass ratio of 96.2:1.0:1.6:1.2, thoroughly stirred to mix uniformly, and then anode slurry (solid content 63%) was prepared. This anode slurry was prepared at 98 g / m 2 The negative electrode current collector copper foil was coated with the coating material in an amount of 0.1g / g, and then dried, cold pressed, and slit to obtain a negative electrode plate.

[0141] 5. Electrolyte Production At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed according to a volume ratio of 1:1:1 to obtain a mixed solvent, and LiPF6 is dissolved in the mixed solvent to obtain an electrolyte, in which the concentration of LiPF6 is 1 mol / L.

[0142] 6. Secondary battery manufacturing The positive electrode plate, separator, and negative electrode plate are stacked and wound in order, and pre-press molded (during this period, the separator is bonded to the electrode plate) to obtain an electrode assembly. The electrode assembly is then placed inside an outer casing, and the above-prepared electrolyte is added. After going through processes such as packaging, standing, chemical conversion, and etching, a secondary battery is obtained.

[0143] The adhesives and separators, positive and negative plates, electrolytes and secondary batteries of Examples 2 to 18 and Comparative Examples 1 and 2 are the same as those of Example 1, with the difference being that they are manufactured according to the parameters in Table 1.

[0144] The mass ratio of the polyacrylate copolymer to the ceramics in the adhesive of Comparative Example 1 was not within the range of (20-50):(50-80), and the adhesive particle size in Comparative Example 2 exceeded 100 μm.

[0145] A scanning electron microscope image was taken of the adhesive obtained in Example 1, and FIG. 7 was obtained. As can be seen, the adhesive produced in Example 1 of the present application is entirely spherical, with a particle size of about 8 μm.

[0146] The products of Examples 1 to 17 and Comparative Examples 1 and 2 were subjected to the following tests.

[0147] 1.Cold press adhesion: The electrodes and separators in the examples and comparative examples were stacked together and placed on a hot press machine, and the hot press machine parameters were set to 25°C, 10t, and 30s, and pressure was applied to produce and obtain a bonded separator / electrode sample, which was then cut into a rectangular bar of 150 x 20 mm. One side of the rectangular bar electrode was attached to a steel plate with double-sided tape, and the separator and electrode were spaced 2 cm apart from each other at one end of the rectangular bar in the longitudinal direction, to produce and obtain a test sample.

[0148] The steel plate was held horizontally and fixed to the lower fixture of a universal testing machine (Xieqiang Instrument Manufacturing (Shanghai) Co., Ltd., model CTM2100), and the peeled end of the separator described above was fixed to the upper fixture of the universal testing machine and connected to a tensile machine. The test conditions were set to a tensile rate of 20 mm / min and a horizontal pull of 10 cm. After the tensile force became stable, the tensile force value was recorded, and the adhesive strength between the separator and the electrode plate was obtained by the ratio of the tensile force value to the sample width.

[0149] 2. Cycle performance of lithium-ion batteries: Using a LAND battery test system, at 25°C, the batteries produced in the examples and comparative examples were charged at a constant current of 1 / 3C to 4.3V, then charged at a constant voltage of 4.3V until the current reached 0.05C, left to stand for 5 minutes, and then discharged at 1 / 3C to 2.8V, and the resulting discharge capacity was recorded as the initial capacity C0. The above steps were repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle was recorded at the same time. The battery capacity retention rate after each cycle Pn = (Cn / C0) x 100%. That is, the battery capacity retention rate at a specific number of cycles can be used to show the difference in cycle performance.

[0150] 3. Electrode assembly hardness: The electrode assemblies in the examples and comparative examples were placed on a base with both ends horizontal, the width of the hollow area in the middle was fixed at 12 cm, and the electrode assembly was laid naturally flat. The width by which the center position of the electrode assembly was shifted from the horizontal reference line was measured, and the hardness of the electrode assembly was evaluated based on this.

[0151] 4.EIS data: Using Shanghai Chenhua's CHI660D electrochemical station, a sinusoidal voltage signal with a frequency of W1 and a small amplitude is applied to the secondary batteries in the examples and comparative examples, and the system generates a sinusoidal current response with a frequency of W2. The change in the ratio of the excitation voltage to the response current is the impedance spectrum of the electrochemical system in the AC impedance test, the test frequency range is 10mHz to 100kHz, and the amplitude is 5mV. Information such as the real part and imaginary part of the impedance can be obtained at different frequencies through the test.

[0152] The test results are shown in Table 2 below.

[0153] TIFF2025505481000006.tif212169

[0154] As can be seen from Table 2, by comparing the comparative examples with the examples, it is clear from Examples 1 to 17 that the adhesive contains a polyacrylate copolymer, and the resulting adhesive has good adhesive performance, which is suitable for fully exerting its adhesive performance under battery operating conditions, and can further contribute to improving the dynamic performance and safety performance of the battery, and can further improve the battery cycle capacity retention rate. In addition, the core contains ceramics. When this adhesive is coated on a separator and used on a battery, it has strong adhesiveness, improves the cold press adhesive force of the battery core and the hardness of the battery core, reduces the electrochemical impedance, and improves the cycle performance of the battery.

[0155] The mass ratio of the polyacrylate copolymer and the ceramic in the adhesive of Comparative Example 1 was not within the range (20-50):(50-80), and the particle size of the adhesive in Comparative Example 2 exceeded 100 μm. As is clear from Comparative Example 1, when the blending ratios of both are not within the range, the adhesive adhesive strength, JR hardness, battery impedance, cycle performance and magnification performance are all relatively poor, and as is clear from Comparative Example 2, when the adhesive particle size is too large, the adhesive cycle performance and magnification performance are all relatively poor, and the particle size is too large and causes a reduction in adhesive strength, thereby affecting the cycle and magnification performance.

[0156] In summary, when the adhesive proposed in this application is coated on a separator and used in a battery, it has strong adhesion, improves the cold press adhesive strength of the battery core and the hardness of the battery core, reduces the electrochemical impedance, and improves the cycle performance of the battery.

[0157] The above is only a preferred embodiment of the present invention, which does not limit the scope of the present invention, and those skilled in the art can make various modifications and variations to the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the patent protection scope of the present invention. [Explanation of symbols]

[0158] 1 Battery pack 2 Upper case 3 Lower housing 4 Battery Module 5 Battery Cells 51 cases 52 Electrode Assembly 53 Cover plate

Claims

1. 1. An adhesive comprising: a coating layer; and a core disposed within the coating layer, wherein the coating layer comprises a polyacrylate copolymer, and the core comprises a ceramic.

2. 2. The adhesive according to claim 1, wherein the monomers of the polyacrylate copolymer include an acrylate monomer, an acrylonitrile monomer, and an acrylamide monomer.

3. The acrylate monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate, and / or The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and / or The acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide, and / or 3. The adhesive according to claim 2, wherein the molar ratio of the acrylate monomer to the acrylonitrile monomer to the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).

4. 4. The adhesive according to claim 1, wherein a mass ratio of the polyacrylate copolymer to the ceramic is (20-50):(50-80).

5. The ceramic comprises at least one of titanium dioxide, silicon dioxide, boehmite, magnesium oxide and aluminum oxide; and / or 4. The adhesive according to claim 1, wherein the ceramic has a volume average particle diameter Dv50 of 0.01 μm to 2 μm.

6. The adhesive according to any one of claims 1 to 3, characterized in that the adhesive has a volume average particle size Dv50 of 5 to 100 μm, optionally 7 to 8 μm.

7. A method for producing an adhesive, comprising the steps of: adding a monomer of a polyacrylate copolymer to a solution containing an emulsifier to obtain a preliminary emulsion; adding an initiator to the preliminary emulsion to react, and then adjusting the pH value to 7-8 to obtain a reaction liquid; and uniformly mixing the reaction liquid and the ceramics, and then drying the mixture to obtain the adhesive.

8. The temperature of the reaction is between 20 and 90° C., optionally between 75 and 85° C.; and / or The reaction time is between 20 and 40 minutes, and / or The method of claim 7, wherein the drying comprises spray drying.

9. 8. The method for producing an adhesive according to claim 7, wherein the monomers of the polyacrylate copolymer include an acrylate monomer, an acrylonitrile monomer, and an acrylamide monomer.

10. The acrylate monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate, and / or The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and / or The acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide, and / or 10. The method for producing an adhesive according to claim 9, wherein the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).

11. The method for producing an adhesive according to any one of claims 7 to 9, wherein a mass ratio of the polyacrylate copolymer to the ceramic is (20 to 50):(50 to 80).

12. The ceramic comprises at least one of titanium dioxide, silicon dioxide, boehmite, magnesium oxide and aluminum oxide; and / or The method for manufacturing an adhesive according to any one of claims 7 to 9, wherein the ceramic has a volume average particle diameter Dv50 of 0.01 µm to 2 µm.

13. The method for producing an adhesive according to any one of claims 7 to 9, characterized in that the adhesive has a volume average particle diameter Dv50 of 5 to 100 µm, and optionally 7 to 8 µm.

14. A separator, comprising an adhesive according to any one of claims 1 to 6 or an adhesive produced by the method for producing an adhesive according to any one of claims 7 to 13.

15. 14. An electrode plate, comprising an adhesive according to any one of claims 1 to 6 or an adhesive produced by the method for producing an adhesive according to any one of claims 7 to 13.

16. An electrode assembly, comprising at least one of the adhesive according to any one of claims 1 to 6, an adhesive manufactured by the method for manufacturing an adhesive according to any one of claims 7 to 13, a separator according to claim 14, and an electrode plate according to claim 15.

17. A battery cell comprising the electrode assembly according to claim 16.

18. A battery comprising the battery cell of claim 17.

19. 19. A power consuming device comprising a battery cell according to claim 17 or a battery according to claim 18.

Citation Information

Patent Citations

  • Ceramic membrane, application of ceramic membrane to battery and battery comprising ceramic membrane

    CN103035866A

  • A preparation method of a coating modified ceramic separator for lithium ion battery

    CN109192903A

  • Diaphragm slurry, preparation method and application thereof

    CN112259913A

  • Core / shell type fine particle and lithium secondary battery including the fine particle

    JP2006182925A

  • An aqueous composition used for improving a separator for a lithium-ion battery, an improved separator, and a battery

    JP2017525100A